Fault-injection attack on countermeasure algorithms of RSA-CRT cryptosystem - Fanyu KONG; Yong QIAO; Pengtao LIU; Xiaodong LIU; Dashui ZHOU (网络与信息安全学报)
As a widely-applied public-key cryptosystem in TLS,SSL and IPSec protocols,the security of RSA cryptosystem is of great importance.At FDTC 2014,Rauzy and Guilley proposed several improved countermeasure algorithms of RSA implementation based on Chinese remainder theorem,which were used to defeat fault-injection attacks.New fault-injection attacks on two of their countermeasure algorithms are proposed.During the RSA computation process,a permanent fault is injected and then a faulty RSA signature result is induced.The RSA private key can be obtained by using the faulty RSA signature and the correct result.Therefore,Rauzy and Guilley’s two countermeasure algorithms cannot resist our fault-injection attack.